1979
DOI: 10.1113/jphysiol.1979.sp012957
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chloride in quiescent sheep‐heart Purkinje fibres studied using intracellular chloride and pH‐sensitive micro‐electrodes.

Abstract: SUMMARY1. The intracellular Cl activity, a 1 was measured inside quiescent sheep cardiac Purkinje fibres, bathed in normal Tyrode at pH 7 -40, buffered with 22 mMbicarbonate/ 5 % CO2 +95 % 02. The measurements were made using liquid ion-exchanger Cl--sensitive micro-electrodes.2. After internal Cl levels had been depleted by prolonged exposure to Cl-free media (glururonate-substituted) when external Cl was restored, there was a rapid re-accumulation of Cl inside the fibres to levels that were much higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(91 citation statements)
references
References 34 publications
7
83
1
Order By: Relevance
“…It should be noted that this relationship will tend to limit the NH3/NH4+-induced increase in Cl-i at least at the beginning of an exposure. This relationship is opposite to that described in molluscan neurones and cardiac Purkinje fibres (Thomas, 1977;Russell, 1978;Vaughan-Jones, 1979b) but may underlie the decrease in i.p.s.p. driving force in cat motoneurones on intracellular injection of H+ ions (Lux & Schubert, 1969).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…It should be noted that this relationship will tend to limit the NH3/NH4+-induced increase in Cl-i at least at the beginning of an exposure. This relationship is opposite to that described in molluscan neurones and cardiac Purkinje fibres (Thomas, 1977;Russell, 1978;Vaughan-Jones, 1979b) but may underlie the decrease in i.p.s.p. driving force in cat motoneurones on intracellular injection of H+ ions (Lux & Schubert, 1969).…”
Section: Discussioncontrasting
confidence: 42%
“…In addition, the preparation was maintained in a nominally HCO3--free medium where Cl--HCO3-exchange proceeds very slowly (Thomas, 1977;Vaughan-Jones, 1979b). The drugs, however, may bind to a Cl-site, thus explaining their inhibition of exchanges involving Na+ and Cl-ions (Thomas, 1977;Russell, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…reported to slow Cl-reuptake in heart and smooth muscle cells (Vaughan-Jones, 1979;Aickin & Brading, 1984). In rat sympathetic ganglion cells, however, no differences with respect to the normal bathing solution were observed.…”
Section: Gaba and Extracellular Phmentioning
confidence: 74%
“…One possible mechanism of the ai I recovery, described above, would be an efflux of HCO3-in exchange for an influx of Cl- (Vaughan-Jones, 1979;Aickin & Brading, 1984). However, no changes in the kinetics of the at1 recovery after GABA were seen in nominally HCO3--and C02-free, HEPES-buffered solutions (gassed with 100 % 02).…”
mentioning
confidence: 98%
“…Earlier, Furusawa & Kerridge (1927) had measured the pH of cell homogenates and suggested that cat uterine muscle was considerably more alkaline than either cardiac or skeletal muscle. Their method was obviously crude, yet their values for skeletal and cardiac muscle are remarkably similar to those obtained since by direct measurement with pH-sensitive micro-electrodes (Ellis & Thomas, 1976a, b;Aickin & Thomas, 1977a;Vaughan-Jones, 1979;de Hemptinne, 1980). pH-sensitive micro-electrodes clearly can provide the most trustworthy measurements and, in addition, enable continuous recording ofchanges in pHi.…”
Section: Intracellular Ph (Phi) Of the Surface Cells Of Guinea-pig Vamentioning
confidence: 90%